Protestantism and capitalism revisited in the rural highlands of Ecuador - Muratorio, Blanca (1980)
The purpose of this paper is to discuss some of the complexities of the process by which a group of Ecuadorian Indian peasants, recently converted to evangelical Protestantism, is being incorporated into a dependent capitalist economy. As a justifiable reaction against attempts to explain the peasants’ role in the process of change only in terms of ideology (e.g. Erasmus’s ‘encogido syndrome’ or Foster’s ‘image of limited good’), recent Marxist-oriented studies of peasantries [e.g. Cliffe 1977; Raikes 1978; Scott 1976; Ennew, Hirst and Tribe 1977] have emphasised the economic aspects of the interdependence between capitalist and non-capitalist modes of production. However, a Marxist analysis which tries to reveal both the continuous efforts of the ruling classes to maintain and reproduce their domination, and the peasants’ consciousness of their situation, must also give due consideration to political, religious, juridical and ideological practices